Handgrip and functional capacity in Chronic Obstructive Pulmonary Disease patients - Andrea Lúcia Gonçalves da Silva; Eduardo Garmatz; Cássia da Luz Goulart; Lisiane Lisboa Carvalho; Dannuey Machado Cardoso; Dulciane Nunes Paiva
Abstract Introduction: In the Chronic Obstructive Pulmonary Disease (COPD) both pulmonary and systemic condition increase dyspnea, intolerance to exercise and inactivity. Objective: To evaluate possible association between Hand Grip Strength (HGS) and the distance covered in the Six-Minute Walk Test (6MWT) in patients with Chronic Obstructive Pulmonary Disease (COPD). Methods: A cross-sectional study that evaluated 34 patients with COPD from moderate to very severe stages. The HGS test was performed with a manual hydraulic dynamometer (Jamar®, California, USA) with three bilateral measures, allowing 60-seconds rest time in-between measurements. Afterwards, the patients were submitted to the 6MWT along a 30-meters level corridor following the rules of the American Thoracic Society. Results: Average age 62.7±7.2 years old, body mass index 26.7±6.9 Kg/m². The value of the HGS in the dominant hand was 28.0±8.7 Kgf and in the non-dominant hand was 26.7±7.7 Kgf (99.2% of the predicted value and 106.3% of the predicted value, respectively). The subjects covered in average 421.0±110.4 meters in the 6MWT and there has been detected direct and significant correlation between the distance covered and the HGS of the dominant hand (r=0,430; p=0,011) and non-dominant (r=0,502; p=0,002). The patients with COPD that presented lower HGS also covered less distance in the 6MWT. Conclusion: The hand grip strength was directly associated with the functional capacity assessed through the distance covered in the Six-Minute Walk Test in the evaluated trial.